Archeology of ideas in political science and government in Chile (Contextos: Estudios de Humanidades y Ciencias Sociales, 2019)
The limited literature about and reflection on the disciplinary history of Chilean political science is an open topic in the current academy. It is not only so for its descriptive and historic character but also for its evolutionary and historical comprehension and its projection and consolidation as Social Science into social and public affairs. In effect, the work of Valentín Letelier about “La Ciencia Política en Chile y la necesidad de su enseñanza” of 1886 enables us to observe the first vestige about the study and understanding of political science in its era. This is done on the basis of the philosophical precepts of Auguste Comte and the formation of an incipient disciplinary identity until the first half of the 20th century. Thus, the objective in this article is to analyze the impact of the ideas and the historical legacy in the discipline, specifically in the figure of Letelier and his followers. In sum, we try to respond how the development of the political and academic incidence has been of the institutionalization of Political Science in Chile.